Carrier-Free Immobilization of Rutin Degrading Enzyme Extracted From Fusarium spp. - Zang, Yuan-Yuan; Yang, Sha; Xu, Yong-Qiang; Chen, Zhi-Gang; Wu, Tao (Frontiers in Bioengineering and Biotechnology, 2020)
In this study, a strain with rutin degrading enzyme (RDE) activity was screened from moldy tartary buckwheat and subsequently identified as Fusarium spp. The RDE contained was then immobilized by cross-linking to form rutin degrading enzyme aggregates (CLEA-RDE). Then the structural and enzyme characteristics of CLEA-RDE was investigated. Natural deep eutectic solvents (NADESs) were served as hydrolysis solvents, the optimal catalysis conditions of CLEA-RDE in NADESs were then studied. The results of SEM and spectrum showed that compared to free rutin degrading enzyme, CLEA became more stable due to the cross-linking. Meanwhile, CLEA showed a wider pH adaptation and higher stability at low temperature (20 ~ 30 oC) and hydrophobic environment. Orthogonal experiments results showed that pH 5.0 and 40 oC were the optimal hydrolysis condition for degrading rutin with the degradation rate of 10.65 mg﹒min-1﹒L-1. The preparation of CLEA-RDE without a carrier-based immobilization method reduces the loss of enzyme activity, improves the stability of the enzyme and can be applied to the investigation of immobilization of various enzymes, thus providing a referred idea for the improvement of catalysts in industrial production.